Analysis of DNA Polymerases Reveals Specific Genes Expansion in Leishmania and Trypanosoma spp. - Poveda, Ana; Méndez, Miguel Ángel; Armijos-Jaramillo, Vinicio (Frontiers in Cellular and Infection Microbiology, 2020)
Leishmaniasis and trypanosomiasis are largely neglected diseases prevailing in tropical and subtropical conditions. These are an arthropod-borne zoonosis that affects humans and some animals and is caused by infection with protozoan of the genera Leishmania and Trypanosoma, respectively. These parasites present high genomic plasticity and are able to adapt themselves to adverse conditions like the attack of host cells or toxicity induced by drug exposure. Different mechanisms allow these adapting responses induced by stress, such as mutation, chromosomal rearrangements, establishment of mosaic ploidies, and gene expansion. Here we describe how a subset of genes encoding for DNA polymerases implied in repairing/translesion (TLS) synthesis are duplicated in some pathogenic species of the Trypanosomatida order and a free-living species from the Bodonida order. These enzymes are both able to repair DNA, but are also error-prone under certain situations. We discuss about the possibility that these enzymes can act as a source of genomic variation promoting adaptation in trypanosomatids.